Pengaruh Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Universitas Labuhanbatu - Tira syahira, Muhammad Irwan Padli Nasution, Sri Suci Ayu Sundari (CV. Pusdikra Mitra Jaya, 2023)
Effects of Accounting Information System Applications Related to the quality of the financial statements of Labuhanbatu University. This study aims to determine the effect of the application of Accounting Information Systems on the Quality of Financial Statements at Labuhanbatu University. This study uses a descriptive, quantitative approach, with primary and secondary data sources. Data Acquisition Technology Use a questionnaire survey and recording method. The results of this study indicate that the implementation of accounting information systems significantly 77.8% impact on the quality of financial reports.